The complete chloroplast genome of Psydrax latifolia: evolutionary dynamics, comparative genomics and phylogeny - Safhi, Fatmah Ahmed; Jalal, Areej Saud; Alshegaihi, Rana M.; Alshamrani, Rahma; Alamri, Amnah M.; Felemban, Wessam; Abuzaid, Amani Omar; Hussein, Mohammed A. A.; Al Aboud, Nora M.; Magdy, Mahmoud; Abd El-Moneim, Diaa (Frontiers in Ecology and Evolution, 2024)
IntroductionThis study presents the first complete plastome (cpDNA) sequence of Psydrax latifolia, a member of the Rubiaceae family, which includes small trees, smooth shrubs, and occasionally lianas. This specimen was collected near the Red Sea coast in Jazan province, Saudi Arabia, specifically in the paleotropical Fifa Mountains. The research aimed to characterize and compare the plastome of Psydrax latifolia with other species in the Rubiaceae family to enhance our understanding of its evolutionary dynamics and phylogenetic relationships.MethodsThe plastome of P. latifolia was sequenced and reconstructed using whole-genome next-generation sequencing (NGS) techniques. Comparative analyses were performed between the plastome of P. latifolia and 16 other species within the Rubiaceae family to identify genomic features and evolutionary patterns. The plastome structure, gene content, and codon usage were analyzed, with a focus on the Relative Synonymous Codon Usage (RSCU) in different regions of the plastome.ResultsThe plastome of P. latifolia was found to be 153,242 base pairs (bp) in length, including a large single copy (LSC) region of 83,603 bp, a small single copy (SSC) region of 18,115 bp, and a pair of inverted repeats (IRs) of 25,762 bp each. It contained 87 protein-coding genes, 8 rRNA genes, and 33 tRNA genes, with an overall GC content of 37.30%. The RSCU analysis revealed regional variation, with the protein-coding region being more conserved than the intergenic spacer.DiscussionThis study provides the first complete plastome sequence of Psydrax latifolia, offering insights into its genomic structure and phylogenetic position within the Rubiaceae family. Comparative analyses with 16 Rubiaceae species highlighted distinct genomic features and evolutionary patterns. These findings contribute to the understanding of plastome evolution in the Rubiaceae family and provide a valuable resource for future phylogenetic and evolutionary studies.